Pengaruh Kompensasi Terhadap Tingkat Produktivitas pada PT. Summit Oto Finance Cabang Bogor - Yuli Anwar; Abdullah . (Jurnal Ilmiah Binaniaga, 2008)
Providing appropriate and equitable compensation is essential. “ Compensation is intended as retribution (reward) of the company to sacrifice time, energy, and thoughts that have been granted to the company’s employees, then the company duly appreclate the hard work of employees by way of remuneration or compensation in kind ti them. Compensation and not a continuous process that moment. Compensation is a means to anticipate  a situation that could reduce productivity. Employee productivity problems associated also with the  right of every worker to earn a decent living opportunities for people. To be able to enjoy a decent life is not obtainable  without a guarantee of incime and wages that can be generated by the presence of sufficlently high labor productivity. As a reward of productivity achieved karyawan. Rata average compensation inthe form of a basic salary of  Rp 779,568,00, an average allowance of Rp. 1,56,868,00 and the average incentive  ig Rp. 737,057,00. The collection og employee productivity (billing) is obatained from a large collection target value set by the company to be billed to the customer  for which payment is stalled motorcycles and  delinquent payments on certain areas divided by the realization that reached every employee billing in  the month. Employee productivity level of collection in August 2008, the average productivity of employees by 78% of categorized collection baik. Pengaruh compensation to labor productivity levels of labor  in the PT bogor summit Oto Finance Brand as follows : (1) Effect of base salary to the level og labor  productivity sig valuse obtained for 0,237 > a = 0,05 other words there is no influence of the basic salary of labor productivity levels . (2) The effect of the level of work productivity benefits gained sig value of 0,177>a = 0,05 in other woeds there is no effect on the level of work productivity benefits . (3) effect of incentives on the level of labor productivity obtained sig value of 0,002 <a = 0,05 in other words there is an incentive effect on the level of labor productivity.